Glucosinolates in Reseda lutea L.: Distribution in plant tissues during flowering time. (June 2020) - Pagnotta, Eleonora; Montaut, Sabine; Matteo, Roberto; Rollin, Patrick; Nuzillard, Jean-Marc; Lazzeri, Luca; Bagatta, Manuela
Abstract: Reseda lutea L. belongs to the Resedaceae family included in the order of Brassicales. R. lutea is a plant worthy of investigation on an ecological level for its ability to adapt to extreme environmental conditions and for its capacity to attract honeybees and wild pollinators. In the ancient pharmacotherapy it was also known for its healing properties. R. lutea glucosinolates (GSLs) were investigated by HPLC-UV considering their accumulation pattern and their quality profiles during flowering time. 3-Hydroxybenzyl GSL and 2-(α-L-rhamnopyranosyloxy)benzyl GSL were identified by NMR and HPLC-MS of the desulfo derivatives, while benzyl GSL, indol-3-ylmethyl GSL and traces of 2-phenylethyl GSL were identified by HPLC-UV comparison with authentic standards. Our data showed that the uncommon 2-(α-l -rhamnopyranosyloxy)benzyl GSL, until now identified as the main GSL in R. lutea, reached its highest content in the racemes during the full flowering stage, the most pollinator attractive phenological phase of the plant. The 2-(α-l -rhamnopyranosyloxy)benzyl GSL then decreased during late flowering, when the presence of 3-hydroxybenzyl GSL increased. This is the first report of 3-hydroxybenzyl GSL in R. lutea as well as of the full characterization by means of NMR and HPLC-APCI-MS of the desulfated derivative of 2-(α-l -rhamnopyranosyloxy)benzyl GSL. Finally, the identified R. lutea GSL profiles are discussed with reference to the actual knowledge on the Reseda genus GSLs. The results added new evidence to complete the characterization of the GSL profile of this species. Highlights: Glucosinolate investigation of different tissues of Reseda lutea. Isolation of desulfated derivative of 2 and characterization by HPLC-APCI-MS, and NMR. Evaluation of changes in glucosinolate profiles in blooming and fruit ripening phases. Roots of Reseda lutea are a good and stable source of benzyl glucosinolate.